2005
DOI: 10.1037/0021-843x.114.2.216
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of Stopping Performance in Attention-Deficit/Hyperactivity Disorder: Deficient Inhibitory Motor Control?

Abstract: This review discusses whether deficient inhibitory motor control is the core deficit of attention-deficit/hyperactivity disorder (ADHD). Inhibitory motor control is commonly assessed using the stop-signal paradigm. Since the last meta-analysis that was performed, 33 new studies have appeared. The current meta-analysis revealed a significant difference between ADHD patients and matched controls in stop latency (stop-signal reaction time) in both children and adults. Basic reaction time was significantly longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
468
11
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 534 publications
(541 citation statements)
references
References 54 publications
53
468
11
9
Order By: Relevance
“…Regarding the moderator variable age, no significant difference in effect size was found between children and adults with ADHD, indicating that the increase in interference is independent of age. In a meta-analysis of stop-task studies, Lijffijt et al (2005) found that the deficiency in stopping did hardly exceed that in general reaction time in children, whereas it clearly did so in adults. Stroop interference scores, if validly determined, account for differences in general reaction time, but differences in interference between ADHD and control are equal for child and adult samples.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the moderator variable age, no significant difference in effect size was found between children and adults with ADHD, indicating that the increase in interference is independent of age. In a meta-analysis of stop-task studies, Lijffijt et al (2005) found that the deficiency in stopping did hardly exceed that in general reaction time in children, whereas it clearly did so in adults. Stroop interference scores, if validly determined, account for differences in general reaction time, but differences in interference between ADHD and control are equal for child and adult samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individuals with BN who display other impulsive behaviors (e.g., truancy, stealing, drug abuse, multiple sexual partners, self-injury) may have a worse treatment prognosis compared to those without such multiple indicators of impulsivity (Wiederman & Pryor, 1996). Individuals with BN have even been found to show inhibitory control deficits on a stop-signal task (Nederkoorn, Van Eijs, & Jansen, 2004), a computerized neuropsychological measure on which youth with ADHD-C have been established to show deficient performance (Lijffijt, Kenemans, Verbaten, & van Engeland, 2005).…”
Section: Theoretical Rationalementioning
confidence: 99%
“…Furthermore, individuals with BN who display other impulsive behaviors (e.g., truancy, stealing, drug abuse, multiple sexual partners, self-injury) may have a worse treatment prognosis compared to those without such multiple indicators of impulsivity (Wiederman & Pryor, 1996). Individuals with BN have even been found to show inhibitory control deficits on a stop-signal task (Nederkoorn, Van Eijs, & Jansen, 2004), a computerized neuropsychological measure on which youth with ADHD-C have been established to show deficient performance (Lijffijt, Kenemans, Verbaten, & van Engeland, 2005).Third, children with ADHD are at high risk for concurrent problems in parent-child and peer relationships (Asarnow, 1988), two domains that may be related to BN symptoms. It is well documented that children with ADHD have more conflictual relationships with their parents than do children without ADHD (Johnston & Mash, 2001).…”
mentioning
confidence: 99%
“…D1/D5 signalling mediates executive abilities including working memory , attention (Bayer et al, 2000;Granon et al, 2000), motor control (Dreher and Jackson, 1989;Meyer, 1993), and reward and reinforcement mechanisms (Beninger and Miller, 1998). Impairment of those functions is often observed in individuals with ADHD (Arnsten and Li, 2005b;Lijffijt et al, 2005;Luman et al, 2005;Martinussen et al, 2005;Willcutt et al, 2005). Moreover, a recent study in rodents suggested that D1 stimulation contributes to cognitive-enhancing effects of methylphenidate, a leading treatment for ADHD (Arnsten and Dudley, 2005a).…”
Section: Introductionmentioning
confidence: 99%